2009
DOI: 10.1128/aem.00116-09
|View full text |Cite
|
Sign up to set email alerts
|

A NewBorreliaSpecies Defined by Multilocus Sequence Analysis of Housekeeping Genes

Abstract: Analysis of Lyme borreliosis (LB) spirochetes, using a novel multilocus sequence analysis scheme, revealed that OspA serotype 4 strains (a rodent-associated ecotype) of Borrelia garinii were sufficiently genetically distinct from bird-associated B. garinii strains to deserve species status. We suggest that OspA serotype 4 strains be raised to species status and named Borrelia bavariensis sp. nov. The rooted phylogenetic trees provide novel insights into the evolutionary history of LB spirochetes.Multilocus seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
221
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 259 publications
(237 citation statements)
references
References 55 publications
8
221
0
2
Order By: Relevance
“…The percentage of high-fat fully hydrated (H&F), low-fat fully hydrated (L&F), and low-fat moderately hydrated (L&M) Ixodes ricinus ticks that walked towards the wet (light grey bars) or the dry end (white bars) of the arena after 2 h. common one (Casati et al 2004;Jouda et al 2004;Morán Cadenas et al 2007;Gern et al 2010;Herrmann and Gern, 2010). B. bavariensis (6·8%), formerly B. garinii OspA serotype 4, a newly described genospecies (Margos et al 2009), is reported for the first time in the area, although it was already described in Switzerland (Staatswald) (Hu et al 2001;Huegli et al 2002;Pérez et al manuscript submitted ).…”
Section: Borrelia Infection In Ticksmentioning
confidence: 99%
“…The percentage of high-fat fully hydrated (H&F), low-fat fully hydrated (L&F), and low-fat moderately hydrated (L&M) Ixodes ricinus ticks that walked towards the wet (light grey bars) or the dry end (white bars) of the arena after 2 h. common one (Casati et al 2004;Jouda et al 2004;Morán Cadenas et al 2007;Gern et al 2010;Herrmann and Gern, 2010). B. bavariensis (6·8%), formerly B. garinii OspA serotype 4, a newly described genospecies (Margos et al 2009), is reported for the first time in the area, although it was already described in Switzerland (Staatswald) (Hu et al 2001;Huegli et al 2002;Pérez et al manuscript submitted ).…”
Section: Borrelia Infection In Ticksmentioning
confidence: 99%
“…Phylogenetic analysis was conducted using maximum-likelihood (Tamura et al, 2011). Consistent with previous analyses (Margos et al, 2009;Scholz et al, 2013;Takano et al, 2011), European and Asian B. bavariensis sp. nov. formed a sister clade to B. garinii In this context, it is important to emphasize that giving species status to ecotypes of bacteria that form phylogenetically divergent sequence clusters (Koeppel et al, 2008) would have the advantage of being ecologically, epidemiologically and clinically predictive.…”
mentioning
confidence: 99%
“…In the initial study, 10 ospA type 4 strains were included (Table 1). Here, we performed MLSA typing of additional strains isolated from human patients in Europe (Table 1) as described previously (Margos et al, 2009). This typing scheme is based on eight chromosomally located housekeeping genes, clpA, clpX, nifS, pepX, pyrG, recG, rplB and uvrA (Margos et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Borrelia burgdorferi (B. burgdorferi) [14] is found in North America and Europe and is pathogenic to humans. B. garinii [1], B. afzelii [5] and B. bavariensis [20] are found in Europe and East Asian countries and are also pathogenic [45]. kurtenbachii, B. finlandensis and B. yangtze) have also been reported, but the pathogenecity of these Borrelia spp.…”
mentioning
confidence: 99%